1974
DOI: 10.1113/jphysiol.1974.sp010646
|View full text |Cite
|
Sign up to set email alerts
|

Inward movement of sodium ions in resting and stimulated frog's sartorius muscle

Abstract: SUMMARY1. Paired frog sartorius muscles were exposed to Ringer solutions labelled with 22Na+ for about 20 min. At the end of this exposure one of them was stimulated supramaximally one hundred to two hundred times. Immediately after the stimulation both members of the pair were washed in a series of tubes filled with a Na+-free medium containing 3 x 10-5 M strophanthidin.2. Under the above conditions the intracellular component of the efflux was exponential with an average time constant (r) of 388 min, that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…This conclusion could help to support the hypothesis of Caille et al (1978) who suggested the existence of such a mechanism to account for the current-dependent component of the muscular contraction. From the results of Hodgkin & Horowicz (1959) and Venosa (1974) the sodium influx during a normal action potential leads to an increase in the internal sodium concentration of 10-5 M. So the degree of activation of the contractile apparatus by such an amount of sodium ions seems to be too small to play a role during a normal action potential. Thus the sodium-induced calcium-release described in the present experiments might not account for the tension generated by the tubular sodium current described by Caille et al (1978) in normal physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion could help to support the hypothesis of Caille et al (1978) who suggested the existence of such a mechanism to account for the current-dependent component of the muscular contraction. From the results of Hodgkin & Horowicz (1959) and Venosa (1974) the sodium influx during a normal action potential leads to an increase in the internal sodium concentration of 10-5 M. So the degree of activation of the contractile apparatus by such an amount of sodium ions seems to be too small to play a role during a normal action potential. Thus the sodium-induced calcium-release described in the present experiments might not account for the tension generated by the tubular sodium current described by Caille et al (1978) in normal physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced contractility in nonfatigued muscles at lowered [Na ϩ ]o was largely due to 1) an increased number of inexcitable fibers and threshold for action potentials, 2) a reduction of action potential amplitude, and 3) a reduced capacity to generate action potentials throughout trains. sodium gradient; muscle contraction; action potential train; extensor digitorum longus; soleus DURING REPETITIVE ACTIVATION of skeletal muscle, a net influx of sodium ions (Na ϩ ) occurs down their electrochemical gradient during each action potential (13, 25,29). The plasma [Na ϩ ] is usually unchanged or undergoes only a small increase during exercise (24)(25)(26).…”
mentioning
confidence: 99%
“…Here this issue is addressed from the perspective of the effect of lowered [Na ϩ ] o /[Na ϩ ] i ratio on force production. An inward Na ϩ current generates the upstroke of the muscle action potential (10,25,29), and the driving force for the Na ϩ current is the difference between the membrane potential (E m ) and the Na ϩ equilibrium potential (E Na ), where E Na ϭ RT/F ⅐ log e ([Na ϩ ] o /[Na ϩ ] i ). Considering that the gas constant (R) and the Faraday constant (F) are fixed values, then at a given temperature (T) the determinant of E Na is the ratio [ Fast-twitch muscle has lower fatigue resistance than slow-twitch muscle.…”
mentioning
confidence: 99%
“…On the other hand, the magnitude of dV m,max /dt, an expression of the inward I Na during the upstroke of the AP, in P 0.5 was not different from that in P 1 , because the swelling in P 0.5 , and the consequent fall of both (Venosa, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Determination of the extra Na + influx per impulse (J i Na ) with 22 Na + (New England Nuclear, Boston, MA, USA) was done using a technique previously described (Venosa, 1974;Kotsias and Venosa, 2001 Key words: muscle, hypotonicity, membrane potentials.…”
Section: Methodsmentioning
confidence: 99%